Transtorno do espectro autista e intervenção mediada por pares: aprendizagem no contexto de inclusão - Ramos, Fabiane dos Santos (2019)
National and international literature have shown that the pedagogical practices of teachers of students with autism have been ineffective in the school inclusion process. In this sense, Peer-mediated Intervention (PMI) can be a promising alternative, since it is prominent in the international scenario, favoring the student's social skills with autism. Studies have also shown that PMI assists classroom teachers in pedagogical mediation with other peers and it is likely to be implementable in naturalistic environments, such as in school. However, there are few studies addressing the effectiveness of PMI in pre-academic and formal skills of these students. In this perspective, the present study aimed to investigate the effects of PMI on learning process of students with autism in a public school in Santa Maria/RS. This is an interventional research, characterized as a quasi-experimental study of a within-subject single-case. Two students with autism who enrolled in the first and second grades of elementary school, four typical peers and a special educator participated in the study. Data were collected by filming the colleagues acting as support to the student with autism in 20-minute-long classroom activities. PMI (peer instruction) was initially considered as the independent variable of the survey, while the Peer-mediated Behavior (Redirection and Encouragement) was the dependent variable. Thus, the Peer-mediated Behavior becomes the independent variable, while the Task Engagement Behavior (On task/Off task) becomes the dependent variable. This analysis was complemented by statistical analysis of the effect size (Tau-U), both on the peer-mediated behavior and task engagement. Academic learning was also evaluated qualitatively through the collection of the tasks performed by the students during the classroom intervention (activity portfolio) and identification, association and letter naming test at the beginning and end of the study. Results showed that PMI produced socially relevant effects on Peer-mediated Behavior; however, only 38% of the baseline measures had no overlapping with the intervention measures (Tau-U = 0.3814), showing low statistical significance. The effect of PMI on task engagement was statistically significant (Tau-U = 0.6735). As for academic learning, only João responded, which resulted in gains in identifying vowels and naming consonants. The task portfolio analysis shows a decrease in the visual aid to carry out activities independently by João; while Maria began to handle more school materials such as pencils and sheets due to a longer time of task engagement. Peer-mediated Intervention is a viable practice for students with autism within national reality and can be used as an important resource in the education of students with autism. This study should be replicated in order to increase the number of PMI evidence so that this intervention in the national scenario is widespread.